Impact of conflict-related violence and presence of armed groups on food security: Evidence from longitudinal analysis in Mali - Tranchant, Jean-Pierre; Gelli, Aulo; Masset, Edoardo (International Food Policy Research Institute, 2021)
We assess the impact of conflict exposure on households’ food security in rural areas of Mopti, Mali over the period 2012-17. Our main data source is a unique panel dataset of 1,617 households for which the baseline round was collected before the conflict broke out. We estimate the impact of conflict with a weighted difference-in-differences approach. We find that exposure to high level of conflict-related fatalities within a radius of 50km leads to a reduction of daily calorie intake per adult equivalent of 311 kcal (0.39 SD) and a reduction of dietary diversity score by one food group (0.56 SD). The presence of armed groups leads to lower dietary diversity (by 1.2 food group) but has no independent effect on calories. The negative impact of conflict on dietary diversity is concentrated on households with higher scores at baseline. We also estimate whether receiving food assistance mitigates the impact of conflict. We find that school-feeding protects households facing intense conflict by supporting calorie intake.